EFFECTIVE FACTORS IN POSTPARTUM WEIGHT LOSS: A CROSS-SECTIONAL STUDY - Jenabi, Ensiyeh; Nazari, Mansour; Shobeiri, Fatemeh (Journal of Postgraduate Medical Institute, 2016)
Objective: To determine the effective factors in postpartum weight loss. Methodology: We prepared a cross-sectional study in one of educational hospitals (Fatemieh's Hospital) in Hamadan city in the west of Iran. Two hundred women were included in this study. Weight and body mass index was measured in pre-pregnancy state and again at 6 months postpartum. Effective factors in postpartum weight loss were assessed. The questionnaire included age, education, employment, parity, doing exercise, type of delivery, newborn weight and BMI at 6 months after delivery. Results: Mean age of study participants was 23.3±5.21 years and mean parity was 1.62±0.7. The overall average BMI was 24.2±3.3 before pregnancy and 25.5±3.4 six months after delivery. Pregnant women had an increase in weight of 12.1±3.5 kg and mean weight loss was 6.2 ± 2.9 kg at six months postpartum. Multiple regression analysis revealed that age was having p value 0.001, parity (p value 0.005), height (p value 0.01), gestational weight gain (p value 0.001), pre pregnancy BMI (p value 0.001), type of delivery (p value 0.03) and exercise (p value 0.04). Conclusion: Parameters such as age, parity, exercise, type of delivery, height and gestational weigh gain were significantly associated with postpartum weight loss.